2020
DOI: 10.1111/jpm.12633
|View full text |Cite
|
Sign up to set email alerts
|

Training healthcare assistants working in adult acute inpatient wards in Psychological First Aid: An implementation and evaluation study

Abstract: What is known on the subject Healthcare assistants are untrained and unregistered frontline staff but are expected to be proactive in preventing and responding to ‘untoward’ incidents quickly and efficiently when working within adult acute inpatient psychiatric settings. Healthcare assistants should be trained to provide enhanced care to service users residing in acute psychiatric settings. To date, a training programme in Psychological First Aid has not been expended in such a setting with nonregistered sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Of six studies reporting the length of trainees work experience, half of the school counsellors and medical reserve corps had less than 5 years in employment [ 46 , 53 ], however, nursing home staff and police trainees had more than 14 years’ work experience [ 45 , 56 ]. More than 50% of trainees were educated to degree level in a related discipline (e.g., psychology, social work, nursing, education) [ 44 , 46 , 57 ], and among primary healthcare workers responding to Ebola outbreak less than 10% were educated to diploma level [ 40 ]. More than 50% trainees (community leaders and nursing students) had no prior disaster or emergency experience [ 52 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of six studies reporting the length of trainees work experience, half of the school counsellors and medical reserve corps had less than 5 years in employment [ 46 , 53 ], however, nursing home staff and police trainees had more than 14 years’ work experience [ 45 , 56 ]. More than 50% of trainees were educated to degree level in a related discipline (e.g., psychology, social work, nursing, education) [ 44 , 46 , 57 ], and among primary healthcare workers responding to Ebola outbreak less than 10% were educated to diploma level [ 40 ]. More than 50% trainees (community leaders and nursing students) had no prior disaster or emergency experience [ 52 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even though four studies conducted a randomised controlled trial (RCT) [ 42 , 47 , 52 , 54 ], their randomisation methods were not described in detail. In the seven studies that conducted follow-up evaluations, these ranged from two weeks to six months follow up periods [ 42 , 44 , 47 , 52 , 55 , 56 , 57 ]. Six studies reported using a mixed-method evaluation design and three studies only collected qualitative data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HCAs are already accustomed to taking on responsibilities that remove excessive burdens from GPs and nurses (90,91), and they may be willing to accept the new role within a practice as a result of normative in uences to perform the behaviour (92). Educational interventions will require the development of a standardised national training course to ensure that HCAs acquire the appropriate skills and supervision to administer the tests (93,94).…”
Section: Discussionmentioning
confidence: 99%